Earth Science Education 2. Paleontology Summer Day Camps for Children - Robson, Sean; McCrea, Richard (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1999)
Summary A multi-tiered program of week-long paleontology summer day camps is offered in Saskatchewan for children aged 8-12. These camps provide children with a background in earth science and an appreciation of life's history.